EVALUATION OF FENUGREEK GENOTYPES FOR SEED YIELD AND DOWNY MILDEW RESISTANCE (Journal of Plant Disease Sciences, 2017)
Fenugreek (Trigonella foenum  graecum L.) is affected by many diseases;  downy mildew caused by Peronospora  trigonella Gaum is considered one of the most  destructive and wide spread diseases of the  crop, which is commonly occurring February  and March (Thind, 1942, Gupta ., 2015). et al The infected leaves are easily detected by the  presence of yellow patches on the upper  surface and cottony grayish- violet mycelial  growth on the lower surface of the leaves. The  disease is also reported from Algeria,  Pakistan, United Kingdom and India  (Acharya, 2014). The common methods of  disease managements are use of chemical and  disease resistant variety. However continuous  use of chemicals to control plant diseases is  neither environmentally sound nor  economically cheap (Iqbal , 2011). The et al. literature on downy mildew resistant  germplasm of fenugreek is scanty. Therefore  identification of downy mildew resistant /  tolerant genotypes of the self pollinated crop  will be useful for development of resistant  cultivars where the disease is prevalent and  causing heavy yield loss.
Keywords: Fenugreek, Screening, Downy mildew, Seed yield Peronospora trigonella